KARAKTERISTIK ALIRAN DI SEKITAR SILINDER SIRKULAR DAN SILINDER BERSIRIP - Sudirman Sudirman (POLITALA PRESS, 2019)
The flow through an object will produce flow characteristics that depend on several physical parameters, including; shape, surface conditions, and orientation of the object being crossed. This study, the author uses Gambit 2.4 and Fluent 6.3 software to model finned cylinders with variations in the distance between fin. The cylinder diameter, cylinder length, fin length, and fin thickness are variables that remain constant. The variables that are changed are the distance between fins, namely 10 mm, 14 mm and 18 mm. The numerical simulation in this study was carried out using the 3D-steady flow Reynolds Averaged-Navier Stokes (RANS) and RNG k-ε approaches. The air properties used in STP conditions with a temperature of 28oC are, density (ρ) = 1.17 kg / m3 and viscosity (μ) = 1.85 x 10-5 N.s / m2. Inlet conditions of air flow, velocity inlet 16 m / s and turbulence intensity of 1.56% were applied in the inlet boundary condition of the numerical simulation domain. The fluid flow through the cylinder which has a clearance between the cylinder and the wall does not form a pair of vortices with a closed loop direction as is generally the 2D flow vortex behind the circular sililnder. Vortex is formed on the gap between the fin, especially in the gap between the fin near the clearance between the cylindrical fin and the wall. The more vortices that are formed, the greater the induced drag will be, especially in finned cylinders with narrower spacing between fin. Finned cylinders produce a longer wake area before the attached flow occurs.